2017
DOI: 10.1016/j.taap.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Moving into advanced nanomaterials. Toxicity of rutile TiO2 nanoparticles immobilized in nanokaolin nanocomposites on HepG2 cell line

Abstract: Immobilization of nanoparticles on inorganic supports has been recently developed, resulting in the creation of nanocomposites. Concerning titanium dioxide nanoparticles (TiO NPs), these have already been developed in conjugation with clays, but so far there are no available toxicological studies on these nanocomposites. The present work intended to evaluate the hepatic toxicity of nanocomposites (C-TiO), constituted by rutile TiO NPs immobilized in nanokaolin (NK) clay, and its individual components. These na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 42 publications
2
25
2
Order By: Relevance
“…Furthermore, premutagenic lesions, as the ones detected by the comet assay, may be removed by an efficient DNA repair system before their conversion to mutations or chromosome breaks (i.e., the lesions detected in the MN test). In agreement, Bessa et al [62] and El Yamani et al [63] observed that DNA damage induced by TiO 2 NPs on A549 and HepG2 cells decreased from 3 to 24 h, indicating a potential induction of DNA repair pathways after the first few hours of exposure.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, premutagenic lesions, as the ones detected by the comet assay, may be removed by an efficient DNA repair system before their conversion to mutations or chromosome breaks (i.e., the lesions detected in the MN test). In agreement, Bessa et al [62] and El Yamani et al [63] observed that DNA damage induced by TiO 2 NPs on A549 and HepG2 cells decreased from 3 to 24 h, indicating a potential induction of DNA repair pathways after the first few hours of exposure.…”
Section: Discussionsupporting
confidence: 74%
“…29 It is now known that the intracellular approach of apoptosis is mainly initiated by the induction of p53 as a response to DNA damage induced by genotoxic agents. 29 A number of studies have shown that nano-TiO 2 can induce DNA damage and adversely affect both major DNA repair mechanisms: base excision repair and nucleotide excision repair, showing a genotoxic potential to human cells 10,31,[42][43][44][45] and animal models. 24,46,47 We also found that the four sizes of nano-TiO 2 could induce significant DNA damages and micronuclei in human BEAS-2B cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, numerous publications have demonstrated the interference of TiO 2 NMs in a wide range of biological assays, which may then lead to false-positive or false-negative results (Azqueta et al 2015, Di Bucchianico et al 2016, Ferraro et al 2016, Bessa et al 2017, Li et al 2017). In the current study, we have therefore described and taken into account various sources of interference within our assays.…”
Section: Accepted Manuscriptmentioning
confidence: 99%